[Letter] Alliance High School, Kikuyu, Kenya Colony ... to ... H.M. Grace - Francis, Edward Carey (Adam Matthew Digital, 1944)
Ms. letter outlining the situation in Kikuyu and staffing requirements for the school, and setting out the characteristics of the ideal member of teaching staff